Use of ICT for securing libraries and information resources against vandalism in university libraries in the era of global insecurity (2020)
Vandalism of library and information resources is an international problem as well as a historical one that affects all type of libraries. Therefore, the use of ICT for securing libraries and information resources is inevitable. ICT is the only means of securing library resources in the era of global insecurity. Security of libraries and information resources becomes a concern for the modem well equipped libraries. The application of ICT in the library will help in providing quality services by the librarians through the Internet to users as information will be processed and communicated to users to meet their information needs without delay. The methods for securing libraries and information resources against vandalism in the era of global insecurity are through digitization of information resources, electromagnetic and Radio Frequency Identification (RFID), video surveillance and closed- circuit television (CCTV) systems in the library as means to deter crime and ensure safety of information resources in the library. Meanwhile, Lack of fund, poor policies and procedures, natural disasters such as earthquake, flood, fire, storm among others serve are causes of vandalism of library materials. It was therefore, recommended that government should assist the University in providing sufficient funds to install modem security systems to prevent vandalism in the library.